2010
DOI: 10.1016/j.csda.2010.02.017
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of design and model selection methods for supersaturated experiments

Abstract: Various design and model selection methods are available for supersaturated designs having more factors than runs but little research is available on their comparison and evaluation. In this paper, simulated experiments are used to evaluate the use of E(s2)-optimal and Bayesian D-optimal designs, and to compare three analysis strategies representing regression, shrinkage Various design and model selection methods are available for supersaturated designs having more factors than runs but little research is avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 28 publications
2
52
0
8
Order By: Relevance
“…Both E(s 2 )-and D-optimal designs can be found numerically, using algorithms such as columnwisepairwise [59] or coordinate exchange [71]. From simulation studies, it has been shown that there is little difference in the performance of E(s 2 )-and Bayesian D-optimal designs assessed by, for example, sensitivity and type I error rate [67].…”
Section: E(smentioning
confidence: 99%
See 3 more Smart Citations
“…Both E(s 2 )-and D-optimal designs can be found numerically, using algorithms such as columnwisepairwise [59] or coordinate exchange [71]. From simulation studies, it has been shown that there is little difference in the performance of E(s 2 )-and Bayesian D-optimal designs assessed by, for example, sensitivity and type I error rate [67].…”
Section: E(smentioning
confidence: 99%
“…, β d , with the value of τ 2 reflecting the quantity of available prior information. However, the optimal designs obtained tend to be insensitive to the choice of τ 2 [67]. Both E(s 2 )-and D-optimal designs can be found numerically, using algorithms such as columnwisepairwise [59] or coordinate exchange [71].…”
Section: E(smentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Li et al (2010) proposed variable selection methods based on cluster analysis, Edwards and Mee (2011) constructed a randomization test method, and Koukouvinos et al (2011) proposed using entropy measures for variable selection. Other methods for the data analysis of supersaturated designs have been discussed by, for example, Abraham et al (1999), Beattie et al (2002), Li and Lin (2003), Cossari (2008), and Marley and Woods (2010). See Georgiou (2014), in which a review of the construction and analysis of supersaturated designs was provided.…”
Section: Introductionmentioning
confidence: 99%